The Efficacy of Combination Extract Andrographis peniculata and Syzygium polyanthum on Glucose Uptake in Skletal Muscle in Diabetic Rats - Fatmawati Karim; Ester Gonzales Panserga; Mgs Irsan Saleh (HM Publisher, 2018)
Insulin resistance is impaired insulin signaling cascade in target cells to respond normal or elevated circulating insulin to the final cellular effect, such as translocation of vesicles containing GLUT4 glucose transporters, which is the major mediator of glucose removal from the circulation and a key regulator of whole-body glucose homeostasis. Among the several plants, Andrographis peniculata (sambiloto) and Syzygium polyanthum (Daun salam). In the present study, a combination was made, Andrographis peniculata (sambiloto) and Syzygium polyanthum (Daun salam), and to determine the effects of combination on tretament insulin resistance. Male Wistar rats (weight, 200-300 g) were randomized into five groups (6 rats/group). Group 1: negative group. Group 2: positive group (metformin 63 mg/kgBW ). Group 3,4 and 5: treatment with extract combination, each group 250 mg/kgBW, 500 mg/kgBW and 1000 mg/kgBW. Rats were induced by high fat diet-glucocorticoid for insulin resistance. Insulin and GLUT-4 were assayed by ELISA. Treatment with extract combination (250, 500 and 1000 mg/kgBW) and metformin for 2 weeks showed a sigificant decrease in fasting plasma insulin compare with the negative control rats with a reduction of 11,2%, 33,6%, 20% and 19,4%, respectively. Two weeks treatment either extract combination or metformin in diabetic rats, significantly increased GLUT 4 level (p<0,05) with a percentage increase of 6,68%, 15,21%, 12,76% and 1,77%.